Le moi des autres: les sources de la polyphonie narrative chez les écrivaines africaines - Cuasante Fernández, Elena (Verbum – Analecta Neolatina, 2007)
One of the main characteristics of feminine literary texts from black Africa is the dominant use of the first person as a narrative instance of the story. In this work we will try to show how the homodiegetic narrative of the first texts of women writers offers a series of specific features that refer, on the one hand, to the plural value of the use of the first person in non-fiction texts, and, on the other hand, to the introduction, in fiction texts, of new mechanisms of gender identification as polyphony or dialogic communication between women.